THE EFFECT OF ONLINE LEARNING AND DIRECT FACE-TO-FACE TO MATHEMATICS LEARNING ACHIEVEMENT - Annisa Putri Majidah; Leni Marlena (KALAMATIKA Jurnal Pendidikan Matematika, 2021)
This study aimed to determine the effect of learning media on student achievement in mathematics. The learning media used include learning using Zoom Meeting, Google Classroom, and face-to-face in class. The research method used was an experiment with a quantitative approach. The samples were 30 Year 9 students divided into three different treatments in learning: learning using Zoom Meeting, learning using Google Classroom, and face-to-face learning in class. The instrument used was a description of the essay questions used to measure student achievement. Data were analyzed using one-way ANOVA and Tukey's - HSD test. The results showed a significant or different effect between the use of learning media on student achievement (Fcount = 3.665 > Ftable = 3.35) of α= 5%. Furthermore, further tests were carried out using the Tukey's - HSD test to examine which learning media had a different effect. Further test results showed that learning using Google Classroom with face-to-face learning in the class had a different effect on students' mathematics learning achievement. Meanwhile, student achievement between Zoom Meeting and face-to-face learning and Zoom meeting and Google Classroom was not significantly different. The average student learning achievement in face-to-face learning was greater than those using Google Classroom.